Perilaku pembelian impulsif remaja pengguna tiktok shop : Ditinjau dari mindfulness - Hardini, Savira Aprina; Sandri, Ritna; Widodo, Rinto Wahyu (Journal of Indonesian Psychological Science (JIPS), 2023)
ABSTRACT : The shopping system has undergone changes and advancements, particularly with online shopping. Online shopping is considered time-saving and more efficient, leading to an increase in online stores offering attractive incentives such as free shipping and discounted prices. One application that can be used for online shopping is TikTok Shop. This study examines the relationship between mindfulness and impulsive buying behavior among adolescent users of TikTok shops in Malang City. The research adopts a quantitative approach. Accidental sampling is employed as the sampling technique, with a sample size of 100 respondents. The results of the study demonstrate the reliability of both variables. Hypothesis testing indicates a significant relationship between mindfulness and impulsive buying behavior among adolescent users of TikTok Shop in Malang City.KEY WORDS:  impulsive behavior; impulse buying; teenagers; TikTok shopABSTRAK : Saat ini, sistem belanja telah mengalami perubahan dan kemajuan terutama dengan munculnya belanja online. Belanja online dianggap dapat menghemat waktu dan lebih efisien, sehingga semakin banyak toko online yang menawarkan penawaran menarik seperti pengiriman gratis dan harga diskon. Salah satu aplikasi yang dapat digunakan untuk belanja online adalah Tiktok Shop. Penelitian ini bertujuan untuk menjelaskan hubungan antara keadaan pikiran sadar (mindfulness) dan pembelian impulsif pada pengguna remaja Tiktok Shop di kota Malang. Metode penelitian yang digunakan adalah metode kuantitatif. Teknik pengambilan sampel menggunakan accidental sampling dengan jumlah responden sebanyak 100 orang. Hasil penelitian menunjukkan bahwa kedua variabel tersebut dapat diandalkan. Hasil pengujian hipotesis menunjukkan adanya hubungan antara keadaan pikiran sadar (mindfulness) dengan pembelian impulsif pada pengguna remaja Tiktok Shop di kota Malang. KATA KUNCI : perilaku implusif; pembelian impulsif; remaja; TikTok shop Copyright ©2023. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0